1997
DOI: 10.1074/jbc.272.47.29735
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Ligand-binding Site on the Granulocyte Colony-stimulating Factor Receptor by Molecular Modeling and Mutagenesis

Abstract: Granulocyte colony-stimulating factor (G-CSF) initiates its effects on cells of the neutrophil lineage by inducing formation of a homodimeric receptor complex. The structure of the G-CSF receptor has not yet been determined, therefore we used molecular modeling to identify regions of the receptor that were likely to be involved in ligand binding. The G-CSF receptor sequence was aligned with all the available sequences of the gp130 and growth hormone receptor families and a model of the cytokine receptor homolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
32
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 60 publications
4
32
0
Order By: Relevance
“…The major contacts between each G-CSF molecule and the CRH domain occur at the loop regions of a single CRH domain that project into the space between the two FN-III-like repeats. As described above, this is similar to the way in which other cytokines of this class bind to their receptors and is consistent with the predictions of mutagenesis experiments that had previously identified amino acids in the CRH loop segments as important for G-CSF binding (22). Each G-CSF monomer also participates in a minor interaction with the second CRH monomer, and these interactions may help stabilize the receptor dimer.…”
supporting
confidence: 72%
“…The major contacts between each G-CSF molecule and the CRH domain occur at the loop regions of a single CRH domain that project into the space between the two FN-III-like repeats. As described above, this is similar to the way in which other cytokines of this class bind to their receptors and is consistent with the predictions of mutagenesis experiments that had previously identified amino acids in the CRH loop segments as important for G-CSF binding (22). Each G-CSF monomer also participates in a minor interaction with the second CRH monomer, and these interactions may help stabilize the receptor dimer.…”
supporting
confidence: 72%
“…The importance of electrostatic interactions in helical cytokine-receptor interactions has been shown by mutagenesis studies (Lopez et al, 1992;Cunningham & Wells, 1993;Kruse et al, 1993;Zurawski et al, 1993;Clackson & Wells, 1995;Graber et al, 1995;Olins et al, 1995) and the electrostatic complementarity of GH to its receptors has also been described (Demchuk et al, 1994: Layton et al, 1997. In the case of the LIF receptor complex, the models of the second CBD of LIFR and the CBD of gp130 showed a very clear electrostatic complementarity over the region that would be expected to dimerize if the complex formed in a manner similar to that of GH-GHR (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…For example, critical ligand binding sites have been found in the corresponding loops of GHR (28), EPOR (24), IL-2R␤ (29), gp130 (13), granulocyte-CSFR (12), and granulocyte-macrophage CSFR (11). Crystal structures of the GHR (9, 28) and EPOR complexes (30,31) have shown that the core of the ligand binding interface is formed by a cluster of hydrophobic residues surrounded by hydrophilic amino acids.…”
Section: Discussionmentioning
confidence: 99%
“…The structure of the growth hormone receptor (GHR) complex (9) has been used as a template for homology modeling of a number of receptors within the family. Subsequent use of such models in designing structure-function studies has led to the identification of potential receptor-ligand contact sites within the granulocytemacrophage colony stimulating factor receptor (CSFR) (11), granulocyte CSFR (12), and gp130 (13). Several hypothetical models of ␥c-containing complexes have also been reported for the IL-2R, IL-4R, and IL-7R (14 -16).…”
mentioning
confidence: 99%